Sailing with Noah : Stories from the World of Zoos - Bonner, Jeffrey P. (Book collections on Project MUSE., 2006)
"An intensely personal, behind-the-scenes look at modern zoos, written in a lively, accessible style. Through a variety of true stories, some funny, some sad, occurring in different cities and on different continents, Bonner describes the changing role of zoos and argues that conservation is the shared responsibility of all mankind"--Provided by publisher